2009
DOI: 10.3844/ajassp.2009.1158.1168
|View full text |Cite
|
Sign up to set email alerts
|

Media Improvement for Hydrogen Production Using C. acetobutylicum NCIMB 13357

Abstract: Problem statement: Some component of fermentation medium showed to reduce the bacterial production of hydrogen. Approach: Reinforced clostridium medium is a selected medium for Clostridium species. Reformulation this medium regarding hydrogen production may focus on such medium composition that enhance or reduce the bacterial productivity. The optimum pH and temperature for hydrogen production were at initial pH of 7.0 and 30ºC. Results: The results show that both nitrogen source and its concentration affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In addition, it is normally found that microorganisms utilize carbon 25–30 times faster than nitrogen. To meet this requirement, a C/N ratio of 20–30:1 is needed . But, the optimum C/N ratio varied depending on types of substrate and microorganism used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is normally found that microorganisms utilize carbon 25–30 times faster than nitrogen. To meet this requirement, a C/N ratio of 20–30:1 is needed . But, the optimum C/N ratio varied depending on types of substrate and microorganism used.…”
Section: Discussionmentioning
confidence: 99%
“…Ammonia nitrogen is regarded as a potential inhibitor during anaerobic digestion, particularly when dealing with complex type of substrates [14].Thus, a negative correlation exists between biogas yield and NH 1 4 -N. In addition, it is normally found that microorganisms utilize carbon 25-30 times faster than nitrogen. To meet this requirement, a C/N ratio of 20-30:1 is needed [28]. But, the optimum C/N ratio varied depending on types of substrate and microorganism used.…”
Section: Discussionmentioning
confidence: 99%
“…The results were analyzed considering the minimization of the Ca þ P content of cells as the optimization criterion (Table 5). From variance analysis (not shown), only the F ratios of Ca, 4.2, was larger than the critical value of F 0.05 (2,18), indicating that only this factor had a significant impact on the mineral content. The magnitude of the variance, expressed in percentage, reflects the significance of the contribution of each factor, hence their ranking, toward this target (Table 6).…”
Section: 5mentioning
confidence: 93%
“…In this study, the minimum MS of the four factors is considered as the experimental error considering that the unbiased estimates of the sum of squares are much smaller than the variance of the other factors. A factor is considered as having an impact which is statistically significant at a probability of 99% and 95% if the F ratio calculated for the factor evaluated is greater than the critical value of the F distribution with 2 and 18 df for a P-value of 0.01 and 0.05, F 0.01 (2,18) and F 0.05 (2,18), i.e. 6 and 3.6, respectively.…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation